2018
DOI: 10.1186/s12879-018-3262-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal vaginal colonization with selected potential pathogens of neonatal sepsis in the era of antimicrobial resistance, a single center experience from Sri Lanka

Abstract: BackgroundMaternal vaginal colonization with antibiotic resistant organisms is a growing concern in countries with high antibiotic resistance rates.MethodsA low vaginal swab was collected from mothers on admission, on discharge and a peri-rectal swab was collected from the neonates born to these mothers on discharge. Routine microbiological methods were used to identify the colonization rates for Escherichia coli, Klebsiella spp. and Streptococcus agalactiae.ResultsThe pre-delivery colonization rate among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
0
17
1
4
Order By: Relevance
“…Another study done among children attending pre-school childcare facilities in Laos has identified 23.2% of the study population to be colonised with ESBL producers [ 25 ]. The rate of colonization we found in the current study is much higher than the rate of vaginal colonization found among pregnant females presenting for delivery at Teaching Hospital Peradeniya [ 26 ]. The differences in sampling sites and study cohorts may be possible reasons for this difference.…”
Section: Discussioncontrasting
confidence: 65%
“…Another study done among children attending pre-school childcare facilities in Laos has identified 23.2% of the study population to be colonised with ESBL producers [ 25 ]. The rate of colonization we found in the current study is much higher than the rate of vaginal colonization found among pregnant females presenting for delivery at Teaching Hospital Peradeniya [ 26 ]. The differences in sampling sites and study cohorts may be possible reasons for this difference.…”
Section: Discussioncontrasting
confidence: 65%
“…The prevalence of GBS observed in this study (6.8% at <20 weeks GA, 10% at the ≥20 weeks GA timepoint in pregnancy, and 27% post-delivery) are in line with the pooled prevalence of a recent meta-analysis report on the prevalence of GBS in pregnant and post-delivery women in Tanzania (16.14%; 95% CI 2.9, 29.4) [ 87 ]. It should be noted that about 1 in 100 infants born from mothers carrying GBS develop invasive GBS infection disease in studies performed on other populations [ 88 , 89 ]. Thus, as evidence on the involvement of pathobionts in maternal and new-born health, and their possible vertical transmission, it is essential to further investigate the association between abundance of GBS, and other pathobionts, and perinatal health.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, as evidence on the involvement of pathobionts in maternal and new-born health, and their possible vertical transmission, it is essential to further investigate the association between abundance of GBS, and other pathobionts, and perinatal health. It is even more so, now that some of these pathobionts strains, like Klebsiella and E. coli , are becoming increasingly resistance to a broad range of antibiotics [ 81 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dissemination of ESBL-GNB in African communities is widespread, with outpatient cross-sectional studies indicating 32.6% carrier prevalence for children in Guinea-Bissau [48], 21.1% prevalence for children in Madagascar [52] and 63.3% carriage prevalence in adults and children in Egypt [53]. Maternal acquisition of GNB temporally related to hospital admission has also been described with rectovaginal carriage prevalence increasing from 18.8% pre-delivery to 41.5% at time of postnatal ward discharge in Sri Lanka [54].…”
Section: Discussionmentioning
confidence: 99%